PENGEMBANGAN PERANGKAT PEMBELAJARA IPA MENGGUNAKAN MODEL KOOPERATIF TIPE STAD DENGAN STRATEGI TALKING CHIPS UNTUK MENINGKATKAN HASIL BELAJAR - Rahmawati, Lukluk; Jatmiko, Budi; Raharjo, Raharjo (JPPS (Jurnal Penelitian Pendidikan Sains), 2016)
The purpose of this research to produce science learning material by using cooperative learning model STAD and talking chips strategy that valid, practical, and effective to improve learning outcomes of  junior high school student?s. The development of learning material use the 4D model and was tested at junior high school students class VIII A, VIII C, and VIII F with One Group Pretest-Posttest Design. The data collection used observation method, test, and quetionnaires. Descriptive data analysis of quantitative-qualitative results are: (1) Learning material on terms of a valid category of: (a) Validation of the instruments very good category (3,78), (b) Readability of book (92,9%) and worksheets (95,18%) are easier category for student?s; (2) Learning material on terms of practical category in: (a) Feasibility of instruction good category, (b) Obstacles for learning can be overcome; (3) The learning material effectiveness on terms of: (a) The response of student?s positively (96,3%), (b) Student?s activity is active category, (c) Student?s learning achievement increased the average of N-Gain 0,71 with high category. The analysis results of  statistic suggests that there is a difference between the learning outcomes before and after implementation of STAD cooperative models with talking chips strategy. The conclusion of this research that the model of cooperative learning STAD with talking chips strategy are eligible to improve learning achievement of junior high school student?s. The implications of this research are becoming students more daring to express opinions and be able to improve student learning outcomes of knowledge competence. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran IPA model kooperatif tipe STAD dengan strategi talking chips yang valid, praktis, dan efektif untuk meningkatkan hasil belajar siswa SMP. Pengembangan perangkat pembelajaran menggunakan model 4D dan diujicobakan pada siswa SMP kelas VIII A, VIII C, dan VIII F dengan rancangan One Group Pretest-Posttest Design. Pengumpulan data menggunakan metode observasi, tes, dan angket. Analisis data secara deskriptif kuantitatif-kualitatif dengan hasil : (1) Kevalidan perangkat pembelajaran ditinjau dari: (a) Hasil validasi perangkat berkategori sangat valid (3,78), (b) Keterbacaan BAS (92,9%) dan LKS (95,18%) berkategori mudah dipahami oleh siswa; (2) Kepraktisan perangkat pembelajaran ditinjau dari: (a) Keterlaksanaan RPP berkategori baik, (b) kendala-kendala selama pembelajaran dapat diatasi; (3) Keefektifan ditinjau dari: (a) Respon siswa positif (96,3%), (b) Aktivitas siswa kategori aktif, (c) Hasil belajar siswa kompetensi pengetahuan meningkat dengan rata-rata N-Gain 0,71 berkategori tinggi. Hasil analisis uji statistik menyatakan bahwa terdapat perbedaan hasil belajar antara sebelum dan sesudah penerapan model kooperatif tipe STAD dengan strategi talking chips. Simpulan penelitian ini, bahwa perangkat pembelajaran IPA model kooperatif tipe STAD dengan strategi talking chips yang dikembangkan layak digunakan untuk meningkatkan hasil belajar siswa SMP. Implikasi penelitian ini adalah siswa menjadi lebih berani mengemukakan pendapat dan dapat meningkatkan hasil belajar siswa kompetensi pengetahuan.